2023
DOI: 10.3390/ijms24108479
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Attenuates Neutrophil ROS Production, MPO Degranulation and Phagocytosis, but Does Not Affect NET Formation Ex Vivo and In Vitro

Shiori Wakasugi-Onogi,
Sihui Ma,
Ruheea Taskin Ruhee
et al.

Abstract: Sulforaphane has several effects on the human body, including anti-inflammation, antioxidation, antimicrobial and anti-obesity effects. In this study, we examined the effect of sulforaphane on several neutrophil functions: reactive oxygen species (ROS) production, degranulation, phagocytosis, and neutrophil extracellular trap (NET) formation. We also examined the direct antioxidant effect of sulforaphane. First, we measured neutrophil ROS production induced by zymosan in whole blood in the presence of 0 to 560… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Glucoraphanin treatment also decreased the mRNA expression of Tnf-α and NADPH oxidase and the number of M1-like macrophages in the epididymal adipose tissue of HFD-fed mice [68]. Recently, another ex vivo and in vitro work demonstrated that SFN reduced the release of the pro-inflammatory cytokines TNF-α and IL-6, and myeloperoxidase from azurophilic granules in whole blood, and was able to suppress the phagocytic activity of neutrophils, as well as the production of ROS in whole blood and neutrophils [21]. In turn, chlorophyll supplementation significantly decreased the serum levels of LPS and TNF-α in HFD-fed mice [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucoraphanin treatment also decreased the mRNA expression of Tnf-α and NADPH oxidase and the number of M1-like macrophages in the epididymal adipose tissue of HFD-fed mice [68]. Recently, another ex vivo and in vitro work demonstrated that SFN reduced the release of the pro-inflammatory cytokines TNF-α and IL-6, and myeloperoxidase from azurophilic granules in whole blood, and was able to suppress the phagocytic activity of neutrophils, as well as the production of ROS in whole blood and neutrophils [21]. In turn, chlorophyll supplementation significantly decreased the serum levels of LPS and TNF-α in HFD-fed mice [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that SFN treatment significantly reduced both lipid accumulation and triglyceride content in adipocytes [19] and induced lipophagy through the activation of AMPK-mTOR-ULK1 pathway signalling [20]. Recently, SFN has been shown to attenuate neutrophil reactive oxygen species (ROS) production, myeloperoxidase degranulation, and phagocytosis, as well as decrease the release of proinflammatory cytokines and ROS production in whole blood [21]. Studies addressing the anti-obesogenic effects of SFN in diet-induced obese rodents have reported that SFN administration was able to significantly reduce body weight gain and liver weight, and improved insulin resistance, glucose tolerance, plasma lipid profile and liver steatosis [17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this research investigation selected a maximum dose of 140 mg/kg (3/5 LD50). The doses used in this study were according to previous studies. In previous studies, the SFN dose of 75 mg/kg had an impact on the performance parameters of broilers with a slight decrease as compared to the control group . Previous studies have demonstrated that SFN exerts antioxidant effects at a dose of 280 μM (49.56 mg/kg after unit conversion) .…”
Section: Methodsmentioning
confidence: 99%
“…31 Previous studies have demonstrated that SFN exerts antioxidant effects at a dose of 280 μM (49.56 mg/kg after unit conversion). 32 So, we also chose 50 mg/kg SFN of the dose as an addition. In accordance with the findings of the prior investigation, 33 the duration of Cd exposure in the current study was established as 90 days to induce a subchronic toxicity condition.…”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (1-isothiocyanato-4-methylsulfinylbutane, SFN) is a naturally occurring isothiocyanate (ITC), which is currently the topic of active research due to its attribute as a critical regulator of cellular defenses through the activation or inactivation of vital transcription factors during any cellular stimulatory responses [23,24]. SFN could activate the nuclear factor erythroid 2-related factor 2 (Nrf2) and inhibit the nuclear factor-kappa-lightchain-enhancer of activated B cells (NF-κB), the major transcription factor in regulating cellular responses to inflammation and oxidative stress [20,23].…”
Section: Introductionmentioning
confidence: 99%